Analysis and Case Study for Minimizing Differential Settlements in Piled Raft Foundations - Yu Chuang; Liu Songyu; Zai Jinmin (Deep Foundations Institute, 2005)
"The piled raft foundation is a geotechnical composite construction method, consisting of three elements, piles, raft and soils, which is applied for the foundation in an increasing number. Differential settlements have numerous negative effects on a superstructure in piled raft foundations. Through the analysis of the production mechanism of differential settlements and differential settlements control measures, a method of adjusting pile configurations is presented to control differential settlements. By comparing the measured data and finite element method analysis of one oil storage piled raft foundation, the new method is verified that the differential settlements can be reduced effectively and the inner forces of foundations are more reasonable with varying length pile configurations. The differential settlements can be minimized or even reduced to zero with right pile length.INTRODUCTIONPiled raft foundations are widely adopted for the prominent advantage of limited settlements and adequate bearing capacities. However, there always exits differential settlements in conventional piled raft foundations. The differential settlement is the main cause that produces additional stresses in the structure. Differential settlements have numerous negative effects on a superstructure as well as on a foundation, and should be restricted to allowable limits. How to control the differential settlement is the key interest.An increasing number of structures are founded on piled rafts. For this reason, design strategies that enable an optimized design have a major importance for safety and economy. An optimized design may be defined as a design achieving maximum economy of the solution, that is minimum cost for the installation of the foundation."